## Info

To find the form of the SMF, note that the ratio, Equation 7.2-7, is maximized when the equality holds, which is when

Hm(ju) = K [S(ju) exp(juxo)]* = K S*(ju) exp(-juxo) 7.2.11

The asterisk denotes taking the complex conjugate of the vector (e.g., if S = p + jq, then S* = p - jq).

Now if s(x) is an even function, i.e., s(x) = s(-x), then clearly S(ju) = S(u) is real and even, and S*(ju) = S(u). Thus, Hm(ju) = K S(u) exp(-juxo). It follows that for the even s(x), hm(x) = F-1{Hm(ju)}, and hm(x) = K s(x - xo). If s(x) is not even, then in general, hm(x) = K s[-(x - xo)]. That is, s(x) is reversed in x and shifted some xo (see Figure 7.2-1).

Was this article helpful?

This guide will help millions of people understand this condition so that they can take control of their lives and make informed decisions. The ebook covers information on a vast number of different types of neuropathy. In addition, it will be a useful resource for their families, caregivers, and health care providers.

Get My Free Ebook

## Post a comment